The Potential Roles of Artemisinin and Its Derivatives in the Treatment of Type 2 Diabetes Mellitus - Jiang, Ya-yi; Shui, Jia-cheng; Zhang, Bo-xun; Chin, Jia-wei; Yue, Ren-song (Frontiers in Pharmacology, 2020)
Type 2 diabetes mellitus (T2DM) is a chronic disease that has become a global public health problem. Studies on T2DM prevention and treatment mostly focus on discovering therapeutic drugs. Artemisinin and its derivatives were originally used as antimalarial treatments. In recent years, the roles of artemisinins in T2DM have attracted much attention. Artemisinin treatments not only attenuate IR and restore islet β-cell function in T2DM but also have potential therapeutic effects on diabetic complications, including diabetic kidney disease, cognitive impairment, diabetic retinopathy, and diabetic cardiovascular disease. Many in vitro and in vivo experiments have confirmed the therapeutic utility of artemisinin and its derivatives on T2DM, but no article has systematically demonstrated the specific role artemisinin plays in the treatment of T2DM. This review summarizes the potential therapeutic effects and mechanism of artemisinin and its derivatives in T2DM and associated complications, providing a reference for subsequent related research.